PENGEMBANGAN E-LKPD BERBASIS PROBLEM BASED LEARNING UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS SISWA SMP - Wulan Safitri; Aris Singgih Budiarso; Sri Wahyuni (Jurusan Pendidikan MIPA FKIP Universitas Jember, 2022)
The Covid-19 pandemic has caused several impacts, one of which is in the field of education. Teachers must innovate to develop media to facilitate distance learning systems. One of the media that can be used is E-LKPD based on Problem Based Learning. E-LKPD based on Problem Based Learning, namely learning media that is presented in an electronic format based on Problem Based Learning. This study aims to develop Problem Based Learning-based E-LKPD to improve the science process skills of junior high school students. The type of research used is R&D research with development design using the ADDIE model. The results obtained are that the Problem Based Learning-based E-LKPD that was developed can be used as a learning medium during the pandemic to improve students' science process skills. This is because E-LKPD based on Problem Based Learning contains a problem to be solved by students.